Predictors of coronal caries progression in adults: results from the Prevention of Adult Caries Study. Issue 6 (9th July 2013) - Singh, Mabi; Papas, Athena; Vollmer, William; Bader, James; Laws, Reesa; Maupome, Gerardo; Snyder, John; Blanchard, Peter
Abstract: Objectives: This secondary analysis of data from the Prevention of Adult Caries Study (PACS) assesses risk factors for progression of coronal caries. Methods: Participants ( n  = 983) were adults at increased caries risk with at least one cavitated and one noncavitated lesions who were enrolled in a randomized clinical trial to test the effect of a 10% w/v chlorhexidine varnish coating on caries progression. Calibrated examiners scored tooth surfaces using a modified International Caries Detection and Assessment System (ICDAS) classification at baseline and at 7 and 13 months postrandomization. Potential baseline predictors of caries risk were used in adjusted negative binomial regression models to predict net D2FS increment and in linear regression models to predict the rank‐normalized net D12FS increment. Results: Mean (SD) D2FS and D12FS increments were and 2.4 (3.1) and 2.1 (6.9), respectively. In multivariate analyses, two or more baseline D2 lesions, consumption of acidic drinks, and increasing age were all significantly associated with increased D2FS and D12FS risk. Daily flossing also was associated with increased D2FS risk. More frequent dental care at baseline was associated with significantly decreased caries risk for both increments. Conclusions: The general concordance of risk factors in the D12FS and D2FS models lends support to the hypothesis that the D1 increment is an intermediate stage in the progression to fully cavitated lesions.